Penyuluhan Hukum Tentang Napza dan Pengenalan Rambu Lalu Lintas Usia Dini Bagi Siswa SDN Desa Rumpia Kabupaten Wajo - Makmur, Andi Dadi Mashuri; Muh. Dandy Dwi P. P.; Alya Anindya; Azis, Nurul Widya Amelia; Andi Rendi Sri Wardhana; Surianto; Muhammad Ikramullah (YP-SDI Lamaddukelleng, 2025)
Substance abuse and traffic violations are major issues that can endanger the safety of children in elementary schools. The purpose of this study was to improve students' legal understanding of the risks of substance abuse in Rumpia Village, Majauleng District, Wajo Regency through legal counseling sessions on the risks of substance abuse and the importance of obeying traffic regulations, followed by the placement of posters around the school as additional visual media. The method used was direct counseling with materials that were easy for students to understand. The results of these activities showed an increase in students' understanding and positive attitudes regarding the risks of substance abuse and awareness to comply with traffic regulations better. It is hoped that this program can be an effective preventive measure in building students' character to be legally aware and responsible.